Pengaruh Pembudidayaan Sarang Burung Walet terhadap Peningkatan Pendapatan Masyarakat dalam Perspektif Ekonomi Syariah - Sitti Walida Mustamin; Umi Fatira (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of swallow nest cultivation on increasing community income in the perspective of Sharia Economics (case study in Siwa village). This research is descriptive qualitative research and tends to use a case study approach analysis. This research explores a problem with detailed limitations, in-depth data collection, and includes various sources of information. This research was conducted in Siwa Village, Wajo Regency for 3 months from February to April 2021. Data sources are parties who are considered to be able to provide information about swallow nest cultivation with a business age of more than 5 years, namely 3 people. The results showed that swallow's nest cultivation greatly influenced the increase in income of the Siwa Village community, seen from the lifestyle of the people who began to increase after the cultivation of swallow's nest.